Upaya Pemberantasan Buta Aksara sebagai Strategi untuk Meningkatkan Kualitas Sumber Daya Manusia di Kabupaten Brebes secara Berkelanjutan - Ubaedillah Ubaedillah; Farhan Saefudin Wahid; Diah Sunarsih (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
Literacy is one of the key factors that hinders the development of human resources. To improve the quality of human resources, it is essential to focus on eliminating illiteracy within the population. One of the primary goals of this outreach activity is to enhance the literacy skills of the local community in Sitanggal Village, located in Larangan District, Brebes Regency, Central Java. The residents of Sitanggal Village primarily rely on farming and entrepreneurship for their income. However, due to the village's isolated location, difficult access, and low economic status, many residents face challenges in accessing proper education. As a result, the illiteracy rate in this area is relatively high, further exacerbating the cycle of poverty. To address this issue, a collaboration has been established with the Community Learning Activity Center (PKBM) Danawangsa Sitanggal, which has facilitated the eradication of illiteracy within the community. The literacy skills of the participants were assessed both before and after the program implementation using pre-tests and post-tests. The participants, aged between 35 and 59 years, totaled 50 individuals. The program was conducted in three stages: reading, writing, and arithmetic. Each stage was structured around specially designed teaching modules, employing engaging and interactive methods to ensure the participants' active involvement. The results of the program were highly encouraging. The participants' reading skills improved significantly, rising from 10% to 64%. Their writing skills saw a notable increase from 40% to 82%, and their counting skills improved drastically from 80% to 100%. These improvements highlight the success of the program and demonstrate the positive impact that literacy education can have on enhancing the overall quality of life for individuals in marginalized communities.